Botanical Composition Forage Fodder on Padalarang-Cileunyi Border Toll Road - Rifianda, Nabila Fara Dega; Indriani, Nyimas Popi; Mansyur, Mansyur (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
As time goes on in the land function area, one solution is needed to meet the needs of forage in the livestock sector. The research was conducted in April 2021, and the samples were identified at the Animal Feed and Forage Laboratory at Padjadjaran University.  This research aimed to determine the botanical composition and carrying capacity of the Padalarang-Cileunyi border toll road.  The method used in this research was stratified random sampling with one sample in every kilo meters on both roads randomly using a quadrant of 0.5 m x 0.5 m with a total of 66 samples along 33 km.  The samples were weighed in fresh and then analyzed descriptively.  The carrying capacity of the padalarang-Cileunyi border toll road was 1.63 AU/ha/year with a forage production of 2.70 tons/ha.  In this research, 80 types of botanical species were found with the most botanical compositions being Paspalum scrobiculatum and Polygonum aviculare.Keywords:  botanical composition, forage, carrying capacity, toll road